2023
DOI: 10.1039/d3dt00516j
|View full text |Cite
|
Sign up to set email alerts
|

Constructing MIL-53(Fe)@ZIF-67(Co) binary metal–organic framework hierarchical heterostructure electrodes for efficient oxygen evolution

Abstract: Improving the efficiency of anodic oxygen evolution (OER) is important to solve the global energy crisis and greenhouse problems. In this paper, a preparation method of MIL-53(Fe)@ZIF-67(Co) composite electrode is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…4c of the O 1s XPS spectrum, it could be shown that the dominant peaks of NiCo-ZIF@MIL (1 : 2) originate from the O-H (532.3 eV), C-C]O (531.16 eV), and O-M (530.48 eV). 23,27 Additionally, this interaction between NiCo-ZIF and MIL-100 affects the coordination environment of O, which leads to obvious shis of binding energies (compared with ESI Fig. S3c †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4c of the O 1s XPS spectrum, it could be shown that the dominant peaks of NiCo-ZIF@MIL (1 : 2) originate from the O-H (532.3 eV), C-C]O (531.16 eV), and O-M (530.48 eV). 23,27 Additionally, this interaction between NiCo-ZIF and MIL-100 affects the coordination environment of O, which leads to obvious shis of binding energies (compared with ESI Fig. S3c †).…”
Section: Resultsmentioning
confidence: 99%
“…23 Compared to single MOF materials, dual-MOF materials tend to exhibit higher catalytic activity, due to the fact that the multiphase structure of the double-MOF composites exposes more active sites, and the synergistic interaction between the composites enhances the charge transfer ability, optimizes the conversion of oxygen-containing intermediates, and reduces the free energy, thus improving the catalytic performance of the materials. [24][25][26][27] In general, MIL-100 is synthesized with benzene-1,3,5-tricarboxylic acid as a ligand. Since the hydroxyl group could construct defects and modify the active sites to promote the adsorption of OH − and oxygen-containing intermediates, which improves the OER activity, 28 we chose a hydroxyl dimer as the ligand to prepare Fe-MIL-100.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are highly ordered porous coordination polymers with 2D or 3D structures formed from metal cluster nodes (secondary building units, SBUs) and polydentate organic ligands, 1–4 which are widely used in CO 2 separation, 5,6 sensing, 7 photocatalysis, 8 environmental detection, 9,10 energy conversion 11,12 and other applications. 13 It is worth noting that MOFs are highly versatile platforms to construct highly efficient oxygen evolution reaction (OER) electrocatalysts benefiting from abundant metal sources and organic ligands, large specific surface area, adjustable porosity and tunable functionality.…”
Section: Introductionmentioning
confidence: 99%